Evidence-based nursing and application of Big Data (循证护理与大数据的应用) - YANG Fei (杨菲); ZHOU Dengfang (周登芳); GENG Qingwen (耿庆文); TANG Ling (唐玲); LIN Baoshan (林宝山) (中西医结合护理)
With the continuous progress, innovation and development of infrastructure technologies such as Internet and enterprise mobile informatization in the industrial mobile era, the development of modern information economy and society has been accelerating, entering a new era of information flow and wide application of Big Data. This paper introduced the current status of application of Big Data in medical and nursing settings, and summarized concepts of Big Data, application of Big Data in clinical nursing and nursing research. Medical and nursing workers should enhance their awareness on Big Data and promote the healthy development of clinical nursing and related disciplines. (随着现代技术的发展, 医疗领域的信息化发展已成为必然趋势。本文主要介绍了目前大数据在医疗护理领域的应用现状, 包括大数据的概述、大数据在临床护理中的应用、大数据在护理研究中的应用等, 广大的医务人员应强化大数据发展意识, 以此工作为发展契机, 共同努力积极推动临床护理相关学科健康发展。)